Defragmenting Proses Berpikir Matematis Siswa dalam Menyelesaikan soal Matematika pada Materi Pangkat dan Bentuk Akar - Muhammad Faisal; Hery Suharna; Soleman Saidi (Jurnal Pendidikan Guru Matematika, 2021)
This study aims to describe the defragmenting of mathematical thinking processes based on students' ability to solve mathematical problems in the material rank and root form. This research is a qualitative descriptive study using test and interview methods. The subjects in this study were students of SMA Negeri 3 Tidore Kepulauan amounting to 3 people and students of SMA Negeri 4 Ternate City totaling 3 people based on the level of student ability (each low, medium, and high). The research instrument consisted of test questions on the process of defragmenting. The results showed that: (1) the students included in the category of high mathematical ability process defragmenting carried out 5 times with the same error indication, as well as the process defragmenting in the same way namely defragmenting through reflection, defragmenting through mathematical connections, and defragmenting with the provision of scaffolding. (2) the students included in the category of mathematical ability are in the process of defragmenting which is done 3 to 6 times with an indication of an error that is not much different, and the process of defragmenting in the same way that is, defragmenting through reflection, defragmenting through mathematical connections, defragmenting by giving scaffolding and defragmenting with cognitive conflict formation. (3) Students who are included in the category of low mathematical ability process defragmenting carried out as much as 4 to 8 times with an error indication that is not much different, and the process of defragmenting, in the same way, is defragmenting through mathematical connections, defragmenting through reflection, defragmenting by giving scaffolding and defragmenting with cognitive conflict formation.